The child penalty: Evidence from Spain - Alicia de Quinto; Laura Hospido; Carlos Sanz (SERIEs - Journal of the Spanish Economic Association, 2021)
Using data from social security records and an event study approach, we estimate the child penalty in Spain, looking at disparities for women and men across different labor outcomes following the birth of the first child. Our findings show that, the year after the first child is born, mothers' annual earnings drop by 11% while men's remain unchanged. The gender gap is even larger 10 years after birth. Our estimate of the long-run child penalty in earnings equals 28%, similar to those found for Denmark, Finland, Sweden or the USA. In addition, we identify channels that may drive this phenomenon, including reductions in working days and shifts to part-time or fixed-term contracts. Finally, we provide evidence of heterogeneous responses in earnings and labor market participation by educational level: college-educated women react to motherhood more on the intensive margin (working part-time), while non-college-educated women are relatively more likely to do so in the extensive margin (working fewer days).
Keywords: I24; J13; J16; J21; J22; J31; 330; Gender; Labor supply; Employment; Wages; Fertility differentials ·Parenting; Education